Legal Protection of Consumer Personal Data in Indonesia Fintech Peer-To-Peer Lending Pioneers (Universitas Negeri Semarang, 2022)
The development of the Financial Technology Industry, especially Peer-to-Peer Lending in Indonesia, brings various conveniences as well as risks. With multiple platforms providing Peer-to-Peer Lending services, it also has an impact on the amount of personal data collected by each platform. This can pose a threat related to consumer personal data, such as cases that have recently emerged. Some Peer-to-Peer Lending platforms abuse their customer’s personal data by spreading it to other parties. Things that should not be done considering the loan agreement that has been agreed between the borrower and the Peer-to-Peer Lending platform regarding personal data that must be safeguarded and if urgently requires this data must be approved by the borrower. This research will discuss the legal protection regulations for the personal data of Peer-to-Peer Lending consumers and discuss the policies implemented by one of the pioneers of Peer-to-Peer Lending in Indonesia regarding the importance of protecting consumer personal data. This research is empirical legal research that uses interviews as a source of data. This study used a qualitative approach to collect primary and secondary data. This research will discuss the current legal regulations related to the protection of personal data including the existence of the Personal Data Protection Law and discuss the policy and implementation of Peer-to-Peer Lending pioneers in Indonesia regarding the protection of borrowers’ personal data.